DIVERSITY OF WILD MAMMALIAN FAUNA OF CHENAB RIVERINE FOREST, PUNJAB, PAKISTAN - M. Altaf; A. Javid; Irfan; M. A. Munir; S. Ashraf; M. Umair; K. J. Iqbal; A. M. Khan; Z. Ali (Journal of Animal and Plant Sciences, 2014)
Present study was conducted at head Marala (SA1), head Khanki (SA2) and head Qadirabad (SA3) which are important wetland sites of River Chenab to find out the diversity of the mammalian fauna. SA1 comprises 2816 ha wetland area, SA2 occupies an area of 1200 ha while SA3 spreads over 1620 ha. Linear count method was applied to estimate the populations of various mammalian species and diversity was measured through Shannon-Wiener index. A total of 15 species (11 large mammals and 4 small mammals) belonging to 6 orders, 10 families and 14 genera were recorded from the study area. Shannon-Wiener diversity index for SA1, SA2 and SA3 was 0.860, 0.972 and 0.975, respectively while the census index/ density was 0.0414 at head Marala, 0.0508 at head Khanki and 0.0231 at head Qadirabad. Indian wild boar (Sus scrofa) and small Indian mongoose (Herpestes javanicus) were dominating species of study area.
Keywords: Mammals; Density; Richness; Evenness; Riverine forests; River Chenab